Understanding gender roles and practices in innovation processes - Iradukunda, F.; Bullock, Renee; Rietveld, Anne M.; Schagen, Boudy van (2018)
Banana Xanthomonas wilt (BXW) is a bacterial banana disease that threatens household income and food security in Burundi. Single disease stem removal (SDSR) is a new labour-saving practice that has been introduced to improve BXW control. In this study we aimed to understand how gender roles can influence the scaling up of SDSR to manage BXW.